The impact of biodiesel policy on the availability of cooking oil: An analysis of sustainable food strategies - Arumdhani, Mega Putri (Jurnal Inovasi Pangan dan Gizi, 2025)
Background: Indonesia's biodiesel policy has developed rapidly as a government strategy to reduce reliance on fossil fuels and enhance the domestic added value of palm oil commodities. A growing body of literature suggests that while biodiesel policies can support national energy security and economic growth, they also create potential risks for food security and environmental sustainability. The aim of this study is to analyze the impact of Indonesia’s mandatory biodiesel policy on the availability of cooking oil, a staple food commodity, in the context of sustainable food strategies. Methods: This research employs a descriptive-qualitative approach using a systematic literature review. Data were collected from published studies, government documents, and statistical reports related to biodiesel policy, crude palm oil allocation, and the food supply chain in Indonesia. The analysis focuses on connecting empirical evidence with the four pillars of food security and principles of environmental and social sustainability. Findings: The findings indicate that increased allocation of crude palm oil (CPO) for biodiesel production, primarily incentivized by government subsidies, has decreased the supply available for domestic food consumption. This has led to cooking oil shortages and price surges across several regions in Indonesia. Furthermore, the expansion of oil palm plantations to satisfy biodiesel industry demands has contributed to deforestation, biodiversity loss, and social conflicts involving local communities. Conclusion: The principal conclusion from this study underscores the urgency for a holistic and integrative energy policy reformulation that balances the needs of energy independence, food security, environmental sustainability, and social justice. Novelty/Originality of this article: This article uniquely integrates the analysis of biodiesel policy impacts on food availability with overarching sustainable development frameworks in Indonesia. The study offers new insights by linking policy analysis with food security pillars and sustainability principles, and provides actionable recommendations for policy enhancements that have not been thoroughly explored in previous research.